Implementation of Dynamic Tariffs in the Portuguese Electricity System - Preliminary Results of a Cost-Benefit Analysis - J. T. Saraiva (2016)
The current Portuguese Tariff Code dates from December 2014 and requires that the Distribution Network Operators (DSO), submit to the Portuguese Energy Services Regulatory Agency, ERSE, a plan for a pilot experiment and a Cost Benefit Analysis (CBA) regarding the introduction of dynamic options in the Access Tariffs in Portugal. In view of this request, EDP Distribuicao, the main Portuguese DSO, established a contract with INESC TEC to conduct these studies and to prepare a report to submit to ERSE by June 2016. In this scope, this paper reports the results obtained so far namely regarding the CBA analysis. This analysis includes the identification of critical hours during which dynamic tariffs can be activated, the estimate of the impact of demand transfers to adjacent hours on the electricity market Social Welfare Function, on network losses, on the investment network avoided costs due to the possible deferral of reinforcements or expansions and on the costs of contracting reserves. These items were estimated along a period of 15 years and together with the estimate of the implementation costs of dynamic tariffs were used to conduct the mentioned CBA analysis.